2022
DOI: 10.3847/2041-8213/ac46a1
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Flares: Ejection of Accreted Magnetic Flux through 3D Plasmoid-mediated Reconnection

Abstract: Magnetic reconnection can power bright, rapid flares originating from the inner magnetosphere of accreting black holes. We conduct extremely high-resolution (5376 × 2304 × 2304 cells) general-relativistic magnetohydrodynamics simulations, capturing plasmoid-mediated reconnection in a 3D magnetically arrested disk for the first time. We show that an equatorial, plasmoid-unstable current sheet forms in a transient, nonaxisymmetric, low-density magnetosphere within the inner few Schwarzschild radii. Magnetic flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
181
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(183 citation statements)
references
References 77 publications
2
181
0
Order By: Relevance
“…Among the physical mechanisms proposed as possible origins of the NIR flares such as population of non-thermal electrons, magnetic reconnection and shocks (Dodds-Eden et al 2010;Ponti et al 2017;Yusef-Zadeh et al 2012;Yuan et al 2003), the one the most independent from accretion rate is magnetic reconnection (Ripperda et al 2020(Ripperda et al , 2021. We therefore suggest that the brightest NIR flares of Sgr A* are likely caused by magnetic reconnection.…”
Section: Discussionmentioning
confidence: 78%
“…Among the physical mechanisms proposed as possible origins of the NIR flares such as population of non-thermal electrons, magnetic reconnection and shocks (Dodds-Eden et al 2010;Ponti et al 2017;Yusef-Zadeh et al 2012;Yuan et al 2003), the one the most independent from accretion rate is magnetic reconnection (Ripperda et al 2020(Ripperda et al , 2021. We therefore suggest that the brightest NIR flares of Sgr A* are likely caused by magnetic reconnection.…”
Section: Discussionmentioning
confidence: 78%
“…Regardless, our work shows that applying the BDNK method [27][28][29][30][31] to MHD can be accomplished successfully. 8 The model presented here can be used for studying 7 Our analysis of the equation of state of [4] was performed in the weak field limit in which signatures of anisotropy are small but significant. It would be interesting to also explore the strong field limit in which features of anisotropy are more salient.…”
Section: Discussionmentioning
confidence: 99%
“…4.1 and found that besides the 7 transport coefficients obtained via Kubo formulae, an additional 11 parameters are needed to ensure stable and causal linear perturbations at every angle θ. 7 We have not explored the region of parameter space in full generality and as such it is possible that causality and stability could be enforced with a reduced number of additional coefficients. Regardless, our work shows that applying the BDNK method [27][28][29][30][31] to MHD can be accomplished successfully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…short gamma-ray bursts in the case of stellar mass black holes formed in neutron star collisions (Abbott et al 2017), or in supermassive black hole accretion (Prieto et al 2016). Supermassive black holes, such as M87, feature intriguing flaring activity (Berge et al 2006), which has recently been related to large scale reconnection happening in the vicinity of the black hole (Porth et al 2021;Ripperda et al 2020;Nathanail et al 2020;Ripperda et al 2021a). Such reconnection events are, however, not limited to black holes, but will also occur in over twisted neutron star magnetospheres (Parfrey et al 2013).…”
Section: Introductionmentioning
confidence: 99%